Professional knowledge construction through reflective practice and tutorial supervision - Campos, Joana (2008)
In this paper the implications of the primary school teachers’ education model implemented at the School of Education of Santarém from 2001 up till now are analysed with respect to the perceived implications of the experienced model on their professional knowledge and practice as beginner teachers. The focus of the research goes to the procedures of reflective analysis, feedback and supervision developed during the practicum throughout the whole training curriculum. Some data are presented and analyzed from a longitudinal exploratory study that has been developed focusing on a sample of beginner teachers who experienced the model, initiating their activity: a) Analysis of individual written reflections produced regularly by students (5 per year), within the practicum, and of their interaction with written feedbacks provided by the supervisor’s team on those reflective writings; b) Semi-structured interviews to a smaller sample within this group in order to deepen the understanding of the same issues.